Identifikasi Bakteri Kolorektal Sebagai Faktor Risiko Terjadinya Kanker Kolorektal - Hijral Aswad (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2016)
This study aims to determine the type of bacteria isolated in colorectal tissues and to investigate the KRAS gene mutation in patients with colorectal cancer. The study design was analytical Cross Sectional. The number of samples used 20 stool, 34 tissues in addition to CRC, 42 CRC tissues, 16 normal tissues other than CRC rinsing, rinsing 17 CRC tissues. The method used is cultur. Rapid TMST Test Panel and PCR. Based on the results of research that has been done can be concluded that the highest prevalence of the bacteria present in the colon tumor tissues than normal colon tissues, there are E. coli, K. pneumonia, K aerogenes, P. vulgaris, E aglumerans, Prov. Stuarti, A. faecalis, P. aerogenes, S. epidermidis, S. intermedius, E. faecalis, Staph. Aureus, Staph. Epidermidis dan S. tiphy. Although statistically the influence of bacteria are not significant to the development of colorectal cancer that showed the value of chi square is p = 0,217